Predicting Customers’ Intention to Revisit A Vintage-Concept Restaurant - Usep Suhud; Arifin Wibowo (Journal of Consumer Sciences, 2016)
Restaurants with a vintage concept become an option for urban people who want to enjoy dining out. To present this vintage atmosphere, restaurant management and owners decorated their stores with antiques and anything vintage, such as signboards, utensils, furniture, posters, and even the menu. The objective of this study is to investigate the impact of perceived value, restaurant atmosphere on satisfaction and revisit intention. This study attracted 200 respondents visiting a vintage-concept restaurant. The data were collected in Jakarta and analysed with exploratory and confirmatory factor analyses. As a result, three hypotheses were accepted and two hypotheses were rejected: customer satisfaction was influenced by perceived value and restaurant atmosphere and revisit intention was significantly influenced by customer satisfaction.